(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This paper This article examines the changing value of monuments that date back to the colonial era in Patna, India, using a comparative lens that also covers the change of heritage in Kenya, Malaysia, and the Caribbean through analogous processes. It analyses the ways in which these once colonial buildings have been reinterpreted in post-independence countries, transitioning from being emblems of imperial power to becoming agents of cultural resilience, public memory, and identity creation. The research takes a critical look at important landmarks in Patna, such as the Patna Collectorate, Golghar, and Gandhi Maidan, and compares them to other monuments in the world, such as the Mau Mau memorials and railway museums in Kenya, the municipal buildings and museums in Malaysia, and the plantation estates and military forts in the Caribbean. The research finds recurrent patterns that are present in all of these places. These patterns include grassroots resistance to erasure, practices of selective remembering, and conflicts between the growth of tourism and the revelation of historical truths. The complicated role that heritage plays in the process of nation-building and post-colonial governance is further highlighted by the fact that there are differences in the reactions of institutions, the levels of community engagement, and the policy frameworks. Using archival research, scholarly literature, and international heritage policy papers, the study underlines the need for methods to monument preservation and reinterpretation that are more inclusive and attentive to the environment in which they are being implemented. For the purpose of fostering transnational understanding, the report suggests the incorporation of heritage education into school curriculum, participatory urban planning models that integrate community perspectives, and the use of heritage in cultural diplomacy. In the end, it makes the case that monuments are not static remnants of the past but rather dynamic platforms that communities use to debate identity, justice, and memory in a world that is decolonising.